Efektifitas Kuliah Kerja Nyata (KKN) Dalam Meningkatkan Partisipasi Masyarakat “Studi Kasus Pada Masyarakat Desa Pagaran Tonga, Padang Lawas Utara” - Satria Darma; Zeid Padolly; Winda Meliana Hasibuan; Nurul Huda; Nina Resmaya Dewi; Nur Khalijah; Denggan Hayani Ritonga; Rezkysyahreni Lubis; Alfi Shahrin; Muhammad Syawal Syaputra (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2023)
Community Participation is a form of community participation to allocate their interests in the process of preparing activity plans to be implemented. Community participation is very important, so it really needs to be increased. Increasing community participation has various challenges, this is due to the diversity of people's own ways of thinking. Many things influence people's way of thinking, including environmental factors, educational background, and circle of friends. Therefore, researchers were interested in studying the issue of community participation, so the discussion topic was chosen, namely Increasing Community Participation. The method used is the PAR (Participatory Action Research) method where the entire community participates in the implementation of this research. The results obtained in carrying out the KKN 41 STAIN MADINA work programs achieved 90% results and were declared successful. This can be seen from the changes that occur in society.